PEMBUATAN DESINFEKTAN UNTUK PENCEGAHAN PENULARAN COVID -19 DI DUKUH POMAH DESA RANDUSARI, KECAMATAN TERAS BOYOLALI - YURI UTOMO; TEGAR HARBRIYANA PUTRA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Community Service Activities to organize universities to solve problems that exist in society through Real Work Lectures (KKN). However, the type of KKN activity that is being held this time is somewhat different from the KKN in the previous period due to the Covid19 virus pandemic since early 2020. Various things have been suggested as an effort to prevent the transmission and spread of new types of Covid-19 cases that are now endemic in our lives, one of which is such as the work program proposed by UBY KKN students at Dukuh Pomah, namely spraying disinfectants at people's homes. The conclusion of this activity is that students participating in KKN carry out a work program of spraying disinfectants to anticipate the spread of the Covid19 virus until the implementation procedure stage. The continued purpose of this activity is to help the residents of Hamlet Pomah to remain calm and vigilant in facing this pandemic together